Effects of tax-benefit policy changes across the income distributions of the EU-27 countries and the UK: 2018-2019 (University of Essex, Institute for Social and Economic Research (ISER), 2020)
This paper provides a short country-by-country harmonised analysis - using EUROMOD - of the distributional effects on household disposable income of direct tax and cash benefit policy changes between 2018 and 2019. It is the latest in this series of reports, available as EUROMOD working papers, produced annually on the public release of an updated EUROMOD. At the same time, last year's equivalent report - covering policy changes between 2017 and 2018 - has also been revised to account for the availability of more recent input micro-data, model extensions and corrections and finalised HICP values for 2018. In this paper, we show how changes (or non-changes) in tax-benefit policies have affected household incomes, abstracting from changes in the population characteristics (e.g. increased unemployment) and the distribution of market/original gross incomes in the years under consideration. The tax-benefit policies in a given year refer to those that applied on 30th of June. (...)
Keywords: 330; Steuerpolitik; Steuervergünstigung; Einkommensverteilung; EU-Staaten